The factors influencing obesity among healthcare workers in two public hospitals in Kedah - Fasihah, Azhari (2020)
In Malaysia, the prevalence of obesity is high among healthcare workers and this becomes a problem because they have the responsibility to promote health and prevent obesity. Besides that, obesity is also associated with higher incidences of injuries at the workplace together with higher medical costs, more lost workdays, and reduced productivity at the workplace. The aim of this study was to identify the factors influencing obesity among healthcare workers and to determine the strategies to control obesity. A qualitative research was conducted among 20 obese healthcare workers through individual semi-structured in-depth interviews, and the interviews were audio recorded. Then, the data were transcribed and analysed by using thematic analysis. The results showed that the themes on the factors influencing obesity were mainly dietary behaviour, job stressors, and working conditions. A total of 26 factors emerged from the data, 22 of these factors had been identified in previous studies while four new factors were found in this study. The participants also suggested several strategies to control obesity including improvement in knowledge, motivation, and exercises. However, the extent of the effectiveness of these strategies could not be confirmed in this study and further studies are recommended on this matter. All of the objectives of this study were achieved. This study provides theoretical contributions to Social Ecological Model on the factors influencing obesity among healthcare workers and helps to develop strategies for weight management at the workplace.